FIQIH JINAYAH: KAJIAN TENTANG PIDANA HUKUMAN BAGI PELAKU TINDAK PIDANA MURTAD - Azhar, Muhammad Fadlan; Siregar, Adnan Ali; Rasyid, Muhammad Haekal Hamdi; Harahap, Mora Sakti; Harahap, Himsar Hidayat (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study discusses apostasy as a theological issue in Islam with legal and social implications. Using a normative approach, the research analyzes the views of scholars on the definition, elements, and penalties of apostasy. The findings show that the punishment for apostasy, including the death penalty, aims to preserve the purity of Islam and the stability of the Muslim community, although its application varies. The study also highlights the importance of social context in the implementation of apostasy laws. These findings can serve as a basis for discussions on the relationship between religion and law in Muslim societies